2009
DOI: 10.1007/s00436-009-1339-7
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory study on larvicidal activity of indigenous plant extracts against Anopheles subpictus and Culex tritaeniorhynchus

Abstract: Anopheles subpictus and Culex tritaeniorhynchus have developed resistance to various synthetic insecticides, making its control increasingly difficult. Insecticides of botanical origin may serve as suitable alternative biocontrol techniques in the future. The leaf acetone, chloroform, ethyl acetate, hexane, and methanol extracts of Aegle marmelos (Linn.) Correa ex Roxb, Andrographis lineata Wallich ex Nees., Andrographis paniculata (Burm.f.) Wall. ex Nees., Cocculus hirsutus (L.) Diels, Eclipta prostrata L., a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(37 citation statements)
references
References 45 publications
2
33
0
2
Order By: Relevance
“…This result also agrees with that of Govindarajan et al (2011) who has shown that the larvicidal and ovicidal activities of crude leaf extracts of Ervatamia coronaria and Caesalpinia pulcherrima against A. stephensi, A. aegypti, and C. quinquefasciatus. Our result also agrees with that of Elango et al (2009) who showed that indigenous plant extracts such as Aegle marmelos, Andrographis lineate, Andrographis paniculata, Cocculus hirsutus, Eclipta prostrata, and Tagetes erecta have oviposition-deterrent, ovicidal, and repellent activity against Anopheles subpictus in Vellore District, Tamil Nadu, India. Similarly, Tawatsin et al (2006) too have reported that the relatively high oviposition-deterrent activity was obtained by essential oils of Curcuma longa, Zingiber officinale, V. trifolia, Melaleuca cajuputi, Manglietia garrettii, and Houttuynia cordata.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This result also agrees with that of Govindarajan et al (2011) who has shown that the larvicidal and ovicidal activities of crude leaf extracts of Ervatamia coronaria and Caesalpinia pulcherrima against A. stephensi, A. aegypti, and C. quinquefasciatus. Our result also agrees with that of Elango et al (2009) who showed that indigenous plant extracts such as Aegle marmelos, Andrographis lineate, Andrographis paniculata, Cocculus hirsutus, Eclipta prostrata, and Tagetes erecta have oviposition-deterrent, ovicidal, and repellent activity against Anopheles subpictus in Vellore District, Tamil Nadu, India. Similarly, Tawatsin et al (2006) too have reported that the relatively high oviposition-deterrent activity was obtained by essential oils of Curcuma longa, Zingiber officinale, V. trifolia, Melaleuca cajuputi, Manglietia garrettii, and Houttuynia cordata.…”
Section: Resultssupporting
confidence: 92%
“…After the treatment, the counted eggs from each concentration were individually transferred to stored water cups for the assessment of hatchability. The percent egg mortality was calculated on the basis of unhatched eggs after 98-h posttreatment by employing the following calculation (Elango et al 2009). …”
Section: Ovicidal Assaymentioning
confidence: 99%
“…quinquefasciatus larvae [19][20][21][22] . The extracts from T. erecta had larvicidal activity against Aedes aegypti and against the larvae of Meloidogyne incognita, respectively [23][24][25] but till now there is no report on the toxicity of T. erecta against Cx. quinquefasciatus Say.…”
Section: Discussionmentioning
confidence: 99%
“…Aegle marmelos (L), a tree under the Rutaceae family commonly known as "Bael", is a native plant of India with religious and medicinal importance [7]. The tree has a trunk with spiny branches and green leaves with three leaflets which release a fragrance when bruised [8].…”
Section: Introductionmentioning
confidence: 99%